Your Fried Chicken is “Hot” [but “Stenchy”]! A Business Analysis of PT Fast Food Indonesia, Tbk during the Pandemic - Carissa Firdaus; Resi Ariyasa Qadri (Pusat P2M Politeknik Negeri Batam, 2022)
The Covid-19 outbreak has a severe impact on Indonesia's food and beverage industry. The purpose of the study is to examine the business and growth plan, review the financial situation, and determine the intrinsic value of FAST firm shares. The research employs the case study methodology to fulfill the objectives. The financial and business data are collected via documentation and analyzed using the financial statement analysis framework. Our study finds that the business slows down when the pandemic struck and thus the company take a defensive strategy to sustain its business. Market players seem to overvalue FAST’s stock price. Our research plays a significant role in shedding a light on firm’s fundamental analysis for investors before placing their investment in FAST.